Priprave in izvedba revolucionarnega prevzema oblasti na Slovenskem leta 1945 - Deželak-Barič, Vida (Studia Historica Slovenica, 2016)
This paper deals with the strategy and tactics of the Communist Party of Slovenia (KPS) and the related question of the nature of the revolution on Slovene territory in the context of communist takeover of power. It is based on the findings of previously conducted research and on archival sources. The period in question encompasses the preparatory phase of the KPS for the takeover of power in the last year of occupation, the direct takeover of power towards the end of the war, and the further consolidation of authoritative position of communists in 1945. The paper also analyzes the methods of operation and the fundamental standpoints of the KPS in the last year of the war, which were in the process of preparation for the revolutionary takeover of power. It highlights the key factors that have enabled the KPS to seize the power and deal with the enemy, as well as the tactics of the KPS in the process of assuming power and consolidating key positions.
Keywords: 1944/1945; Komunistična partija Slovenije; NOB; oblast; revolucije; Slovenija